State-of-the-Art Automated Patch Clamp Devices: Heat Activation, Action Potentials, and High Throughput in Ion Channel Screening - Stoelzle, Sonja; Obergrussberger, Alison; Bruggemann, Andrea; Haarmann, Claudia; George, Michael; Kettenhofen, Ralf F.; Fertig, Niels (Frontiers in Pharmacology, 2011)
Ion channels are essential in a wide range of cellular functions and their malfunction underlies many disease states making them important targets in drug discovery. Diverse automated patch clamp systems with high-throughput capabilities are available for drug screening, but there are limitations in the application range. For example, solution exchange time, temperature control and the availability of the current clamp mode can be limiting factors. However, further development of existing devices and introduction of new systems widen the range of possible experiments and increase throughput. Here we introduce new features and platforms that meet the needs of drug discovery researchers and basic researchers alike. The Patchliner is an automated patch clamp system capable of recording up to 8 cells simultaneously with high success rates. Novel features such as temperature control and recordings in the current clamp mode are described here. Standard cell lines and excitable cells such as stem cell-derived cardiomyocytes have been used in the voltage clamp and current clamp modes with the view to finding new drug candidates and safety testing methods in a more physiologically relevant environment. The SyncroPatch 96, is a screening platform capable of recording from 96 cells in parallel and offers a throughput of 5000 data points per day. Full dose response curves can be acquired from individual cells reducing the cost per data point. The system is an ideal tool for secondary screening efforts and for safety testing on ligand- and voltage-gated ion channels. The Patchliner and SyncroPatch 96 are ideal platforms for drug discovery, ion channel research and safety testing, combining long awaited features such as parallel action potential recordings and temperature control with extensively increased throughput.